Analisis Pola Keausan Carbon Strip Pantograf pada Kereta MRT Jakarta - Asia Habby, Fihanas Permada; Tamara, Adrian Kristanto; Dahlan (Jurnal Teknik Transportasi, 2024)
MRT Jakarta is one of the KRL type railway operators in Indonesia. The reliability of MRT Jakarta facilities must always be considered, the service life of components is also one of the keys to the reliability of the facilities. Carbon strip, as one of the main components in KRL operations, is a component that has a lifespan in use. Thickness measurement is a routine activity in carrying out maintenance of facilities at the depot, if the carbon strip is at its maximum wear, the component must be replaced immediately. However, there is a difference in thickness between the two sides of the carbon strip, which shortens its lifespan. If one side is at its maximum wear, then replacement must be made on both sides. This journal will discuss in detail the factors that cause wear and tear and calculate the wear rate and service life of carbon strips using the forecasting method. So it is necessary to change the maintenance method to be able to increase the service life of the components, so as to reduce maintenance costs in one period of time.